2015
DOI: 10.1177/0020852314558028
|View full text |Cite
|
Sign up to set email alerts
|

At the front line: examining the effects of perceived job significance, employee commitment, and job involvement on public service motivation

Abstract: Social welfare work has long been identified as a highly stressful occupation, and one in which considerations of motivating employees and encouraging increased responsibility and commitment are central to understanding individual and collective performance. In the face of organizational factors that negatively affect employees' motivation, including a lack of promotion opportunities, red tape, and expected emotional exhaustion, it becomes much more important for management to motivate employees in such a way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 56 publications
3
17
0
1
Order By: Relevance
“…This proves that the commitment of teachers in school was formed when the teacher felt the workload provided was appropriate. This is in accordance with research by (Kim, Henderson, & Eom, 2015) in a study found that the negative impact of heavy workload and the resulting fatigue on employees' motivation.…”
Section: Discussionsupporting
confidence: 93%
“…This proves that the commitment of teachers in school was formed when the teacher felt the workload provided was appropriate. This is in accordance with research by (Kim, Henderson, & Eom, 2015) in a study found that the negative impact of heavy workload and the resulting fatigue on employees' motivation.…”
Section: Discussionsupporting
confidence: 93%
“…When employees perceive a high degree of task significance, they gain opportunities to fulfil their higher-order needs, such as selfactualization and self-esteem (Wright and Kim, 2004). Perceived job significance has a positive and statistically significant impact on PSM levels, supporting the idea that such perceptions are critical to developing a prosocial orientation and PSM in Korean public sector employees (Kim, Henderson, and Eom, 2015). Employees are particularly motivated by the extent to which their jobs affect the well-being of others and society (Hackman and Oldham, 1980).…”
Section: H2: Task Identity Is Positively Related To Psmmentioning
confidence: 90%
“…It has been taken for granted that public employees joining the public sector with high PSM bring positive behavioral and organizational outcomes (Kim, Henderson, and Eom, 2015;Perry and Wise, 1990). However, it is also possible that employees are attracted to public service professions with different motives.…”
Section: Multiple Incentives and Work Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Bellé (); Christensen and Wright (); Grant (); Kaiser (); Kim (); Stritch and Christensen (); Taylor (); Vogel and Kroll (); Waterhouse, French, and Puchala (); Wright and Pandey (); Wright, Shahidul, and Christensen ().…”
mentioning
confidence: 99%